ANÁLISE MICROBIOLÓGICA DE AMOSTRAS DE ÁGUA DE POÇOS RASOS LOCALIZADOS NO MUNICÍPIO DE BURITIS, REGIÃO DO VALE DO JAMARI, RONDÔNIA, AMAZÔNIA OCIDENTAL - Zan, Renato André; Costa, Alessandro Lima; Costa, Janice Barbieri; Meneguetti, Dionatas Ulises de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707293 More than one billion people in the world lack of fresh water, and human consumption isexpected to double every twenty-five years, and groundwater from shallow wells are increasinglyused for human consumption and the association of various problems health especially in theelderly and children under five. The present study aims to perform microbiological analysis of wellwater in the urban area of Buritis, Rondônia, Brazil. Were collected and analyzed thirty (30)samples of water by means of culture in dish in form of dehydrated gel. It was found togroundwater contamination by total and fecal coliforms, not meeting the standards of potabilityrecommended in Regulation 518/04 for the human consumption representing a risk to health.